Variación estacional en el lago de Río Cuarto, Provincia de Alajuela, Costa Rica. I. Limnología Físico-Química. - Charpentier, Claudia (1988)
Five sampling stations were stablished in lake Rio Cuarto. Three of them were located in the littoral zone with maximum depths of 12, 3 and 0,5 meters; samples were taken every 3 meters, beginning at the surface. The other two stations were in the center of the lake, and the samples taken at 0, 3, 6, 9, 12, 15, 25, 35, 45 and 55 m. This study was done between February 1984 and  March 1985, with monthly sampling. Dissolved oxygen, pH, temperature, free CO2 were the parameters studied. The determination of the morphometry, mixing patterns and stratiphication of this lentic water mass are of a lake, therefore are strongly recommended not to refer to is as a lagoon anymore. It was determined that lake Río Cuarto is meromictic, the vertical mixing occurred between January and February, the thermal stratification was found between 15 and 25 m deep and anoxic layer began at 15 m. In the mixolimnion the oxygen concentration ranged between 8 and 4 mg/l. Yhe average superficial temperature was 27,59 ± 1 °C and compared with the bottom o difference of 3,18 °C was found.